2011
DOI: 10.2478/v10120-011-0017-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrozetes species (Acari, Oribatida) at bog ponds and pools in the Tatra National Park and Orawa-Nowy Targ Basin (Kotlina Orawsko-Nowotarska) in southern Poland

Abstract: Abstract:The Hydrozetes fauna was investigated at the edges of 4 ponds and pools with acid water in southern Poland. Mites of this genus achieved the highest mean abundance (6×10 4 ind./m²) at a pond in the Tatra National Park (Staw Toporowy Niżni; pH = 3.9; 1089 m a.s.l.). H. confervae dominated there (98%), accompanied by H. octosetosus and H. lacustris. The same species were also present at a nearby pond (Staw Toporowy Wyżni; pH 3.9; 1120 m a.s.l.), but in significantly lower numbers. In the bogs of the Ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
(14 reference statements)
1
0
0
Order By: Relevance
“…In contrast, H. lacustris was found only in acidic waters. POPP (1962) considered this species extremely euryionic, but other authors announced its preference for strongly acidic water (WALgRAM 1976;WEIgMANN 2006;WEIgMANN & DEIcHSEL 2006;MISTRZAK et al 2011), which is confirmed in this study. Similarly, H. octosetosus and H. longisetosus were found only in the bodies of water with low pH, but H. longisetosus was absent in the peat pond Ba, possibly due to the higher concentration of sulphur and worse oxygen conditions, in comparison to other water bodies.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, H. lacustris was found only in acidic waters. POPP (1962) considered this species extremely euryionic, but other authors announced its preference for strongly acidic water (WALgRAM 1976;WEIgMANN 2006;WEIgMANN & DEIcHSEL 2006;MISTRZAK et al 2011), which is confirmed in this study. Similarly, H. octosetosus and H. longisetosus were found only in the bodies of water with low pH, but H. longisetosus was absent in the peat pond Ba, possibly due to the higher concentration of sulphur and worse oxygen conditions, in comparison to other water bodies.…”
Section: Discussionsupporting
confidence: 78%